Dietary Ganglioside Reduces Proinflammatory Signaling in the Intestine - John Janez Miklavcic; Kareena Leanne Schnabl; Vera Christine Mazurak; Alan Bryan Robert Thomson; Michael Thomas Clandinin (Journal of Nutrition and Metabolism, 2012)
Gangliosides are integral to the structure and function of cell membranes. Ganglioside composition of the intestinal brush border and apical surface of the colon influences numerous cell processes including microbial attachment, cell division, differentiation, and signaling. Accelerated catabolism of ganglioside in intestinal disease results in increased proinflammatory signaling. Restoring proper structure and function to the diseased intestine can resolve inflammation, increase resistance to infection, and improve gut integrity to induce remission of conditions like necrotizing enterocolitis (NEC) and Crohn's disease (CD). Maintaining inactive state of disease may be achieved by reducing the rate that gangliosides are degraded or by increasing intake of dietary ganglioside. Collectively, the studies outlined in this paper indicate that the amount of gangliosides GM3 and GD3 in intestinal mucosa is decreased with inflammation, low level of GM3 is associated with higher production of proinflammatory signals, and ganglioside content of intestinal mucosa can be increased by dietary ganglioside.